2018
DOI: 10.4236/aid.2018.83011
|View full text |Cite
|
Sign up to set email alerts
|

Low Prevalence of Carbapenem Resistance in Clinical Isolates of Extended Spectrum Beta Lactamase (ESBL) Producing <i>Escherichia coli</i> in North Central, Nigeria

Abstract: Extended Spectrum Beta Lactamase (ESBL) producing Escherichia coli is a global cause of life threatening infections. We determined the presence of ESBL and carbapenemase production in clinical isolates of E. coli and their antibiotic susceptibility. Clinical isolates of community and hospital acquired E. coli from 220 patients seen at a tertiary hospital were evaluated. Antibiotic susceptibility testing was by the modified Kirby-Bauer protocol while ESBL production was determined by the Double Disk Synergy Tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
4
3
1
Order By: Relevance
“…Demographic data showed that female population carried a higher burden of ESBL infections than the male counterpart and the age group most affected is 45 to 58 years. This is in agreement with the report of [20] from Jos, North-Central Nigeria.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Demographic data showed that female population carried a higher burden of ESBL infections than the male counterpart and the age group most affected is 45 to 58 years. This is in agreement with the report of [20] from Jos, North-Central Nigeria.…”
Section: Discussionsupporting
confidence: 93%
“…It is however, higher than 3.3% reported from Gaza strip [2], 11.8% from Macedonia [9]. Our finding is similar to the report of 18.6% by [20] from a neighboring Plateau State, Jos, North-Central Nigeria and 18.5% by [17] in India.…”
Section: Discussionsupporting
confidence: 83%
“…The prevalence in our study is however lower than the 56.7, 70.0, 72, 83.0 and 95.5% reported by Irith et al (2007), Igwe et al (2016), Horsefall et al (2017) Husam et al (2009 and Wani et al (2009), respectively. It is however higher than the 18.6% earlier reported by Onyedibe et al (2018) in Jos. This difference may be attributed to the use of molecular technique in our study as against phenotypic detection in theirs, since the latter is known to be less sensitive compared to the former.…”
Section: Discussioncontrasting
confidence: 65%
“…This indicates that IPM is still a choice drug for the treatment of MDR bacteria in the region. Nevertheless, other similar studies (Onyedibe et al, 2018, Adesola et al, 2020 reported varying levels of resistance (18.6 and 20.6%, respectively) to the drug. This suggests the need for close monitoring, so as to track and control the spread of resistance.…”
Section: Discussionmentioning
confidence: 79%
“…Most multidrug-resistant ExPEC isolated from bacterial infections in Nigeria are ESBL producers harbouring multiple beta-lactamase genes [21][22][23][24]. Moreover, recent studies on carbapenem-resistant Enterobacteriaceae infections in Nigeria have identified multidrug-resistant extraintestinal Escherichia sp.…”
Section: Introductionmentioning
confidence: 99%